Enterprise and economic development in Africa - Nziku, Dina M.; Struthers, John J. (Emerald Publishing Limited, 2021)
Enterprise can revolutionise economic development in Africa. This edited collection provides readers with a new perspective on a continental phenomenon which is still under researched in contemporary academic discussions. An international range of contributions present real-world examples of the impact of entrepreneurial practice on economic development in Africa, drawing on original research, as well as analysis of current enterprise policies and approaches. Enterprise and Economic Development in Africa highlights the forces that lie behind the recent economic progress on the continent, together with in-depth discussion of African entrepreneurship and the role of institutions in economic development. Chapters explore enterprise and economic development issues including rural entrepreneurship, female entrepreneurship, SME networks, youth employment challenges, university-based entrepreneurial promotion, export-led industrialisation and more. This expansive collection extends the critical examinations of entrepreneurship and economic development in Africa to date, highlighting both challenges and opportunities in developing economies in this unique context.